2013
DOI: 10.1152/jn.00187.2013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stimulus-related activity in rat auditory cortex using complex spectral coefficients

Abstract: Krause BM, Banks MI. Analysis of stimulus-related activity in rat auditory cortex using complex spectral coefficients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…If neural responses are loosely phase locked to the stimulus and are independent of spontaneous neural activity, the intertrial variance of neural activity will be increased (Fig. 1C) (Krause and Banks 2013;Truccolo et al 2002). Finally, even if a sensory stimulus does not generate any phase-locked response, it can suppress spontaneous neural activity ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If neural responses are loosely phase locked to the stimulus and are independent of spontaneous neural activity, the intertrial variance of neural activity will be increased (Fig. 1C) (Krause and Banks 2013;Truccolo et al 2002). Finally, even if a sensory stimulus does not generate any phase-locked response, it can suppress spontaneous neural activity ( Fig.…”
mentioning
confidence: 99%
“…1, B and C. The phase resetting theory predicts that intertrial variance should decrease, while the additive response theory does not generate any specific prediction about intertrial variance. For recordings from different cortical areas and under different behavioral states, the intertrial variance of low-frequency LFP has been reported to increase (Krause and Banks 2013;Truccolo et al 2002), decrease (Churchland et al 2010), or remain unaffected (Makinen et al 2005) by sensory stimuli. Therefore, there is no consistent answer about whether sensory stimuli increase or decrease response variance, and it remains unclear whether this heterogeneity is due to differences in cortical areas or whether it even exists among neural populations within the same cortical area.…”
mentioning
confidence: 99%